The roles of interactive multimedia learning android-based application for primary schools teachers / Tjahjo Prabowo...[et.al] - Prabowo, Tjahjo; Suharto, Mohamad; Mulyanto, Mulyanto; Prameswari, Nadia Sigi (2016)
This The obstacles faced by elementary school teachers in the learning process in the classroom is the difficulty to create an effective learning environment that is popular with student, and rises the curiosity. Therefore, Interactive Multimedia Learning Android-based Application is required as a companion for text book so that the result can be maximized. The purpose of this study is to determine the roles of interactive multimedia learning Android-based application for elementary school teachers in the problem faced in teaching activities in the classroom.